1989
DOI: 10.1007/bf00272116
|View full text |Cite
|
Sign up to set email alerts
|

Selective posterior rhizotomy: a long-term follow-up study

Abstract: Fifty-one spastic children who had undergone selective posterior lumbar rhizotomy between 1981 and 1984 were re-examined to determine whether the gains achieved had persisted and to look at other aspects that had not previously been explored in detail. The reduction of tone was maintained in all cases, while motor function continued to improve in 42 cases. Functional gains were greatest in children operated on under the age of 8, but pleasing results were also achieved in older children. Forty-five children co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(55 citation statements)
references
References 3 publications
4
50
1
Order By: Relevance
“…Peacock et al [6]applied this procedure initially to 60 children in Cape Town with spastic cerebral palsy who where followed for up to 7 years postoperatively. Reduced spasticity and functional gains were reported [6, 26, 27, 28]. In a subsequent series, Peacock and Staudt [29]observed decreased muscle tone, an increased range of motion and improved gait using objective measurements.…”
Section: The History Of Rhizotomy For the Treatment Of Spasticitymentioning
confidence: 92%
See 2 more Smart Citations
“…Peacock et al [6]applied this procedure initially to 60 children in Cape Town with spastic cerebral palsy who where followed for up to 7 years postoperatively. Reduced spasticity and functional gains were reported [6, 26, 27, 28]. In a subsequent series, Peacock and Staudt [29]observed decreased muscle tone, an increased range of motion and improved gait using objective measurements.…”
Section: The History Of Rhizotomy For the Treatment Of Spasticitymentioning
confidence: 92%
“…Sensory loss and transient hyperesthesias are often seen after selective posterior rhizotomy, but can be minimized when the percentage of nerve rootlets sectioned is kept to a minimum. In the Cape Town series with a 7-year follow-up, only 3 out of 51 patients had a clinically detectable decrease in sensation [26]. Persistent sensory loss of no clinical significance was noted in 3.8% of patients in another report [62].…”
Section: Complications Of Rhizotomymentioning
confidence: 99%
See 1 more Smart Citation
“…2,11,14,15 It reduces spasticity by decreasing the excitatory input entering the spinal cord after the transection of selected sensory nerves of the cauda equina. 19 Class I evidence supports the utility of SDR for the immediate and permanent reduction of spastic diplegia in patients with cerebral palsy, improving motor function and performance of ADL.…”
Section: 14mentioning
confidence: 99%
“…We have shown that 5 years after surgery, over 80% of 51 patients were still making progress, [1] whereas at 10 years, 97 of 110 patients had improved their patterns of ambulation, although a formal gait analysis was not conducted. [26] Fasano and Broggi [12] have provided anecdotal evidence of functional benefits 15 years after SDR for 80 patients.…”
mentioning
confidence: 99%